Predictors of Women’s Satisfaction with Hospital-Based Intrapartum Care in Asmara Public Hospitals, Eritrea - Meron Mehari Kifle; Filmon Abraham Ghirmai; Soliana Amanuel Berhe; Winta Sium Tesfay; Yodit Teklemariam Weldegebriel; Zebib Tesfamariam Gebrehiwet (Obstetrics and Gynecology International)
Background. Exploring patient satisfaction contributes to provide quality maternity care, but there is paucity of epidemiologic data in Eritrea. Objectives. To determine the predictors of women's satisfaction with intrapartum care in Asmara public maternity hospitals in Eritrea. Methods. A cross-sectional study among 771 mothers who gave birth in three public Hospitals. Chi-square tests were done to analyze the difference in proportion and logistic regression to assess the predictors of satisfaction with intrapartum care. Results. Overall, only 20.8% of the participants were satisfied with intrapartum service. The key predictors of satisfaction with intrapartum care were provision of clean bed and beddings (AOR = 18.87, 2.33–15.75), privacy during examinations (AOR = 10.22, 4.86–21.48), using understandable language (AOR = 8.72, 3.57–21.27), showing how to summon for help (AOR = 8.16, 4.30–15.48), showing baby immediately after birth (AOR = 8.14, 2.87–23.07), control of the delivery room (AOR = 6.86, 2.65–17.75), receiving back massage (AOR = 6.43, 3.23–12.81), toilet access and cleanliness (AOR = 6.09, 3.25–11.42), availability of chairs for relatives (AOR = 5.96, 3.14–11.30), allowing parents to stay during labour (AOR = 3.52, 1.299–9.56), and request for permission before any procedure (AOR = 2.39, 1.28–4.46). Conclusion. To increase satisfaction with intrapartum care, maternity service providers need to address the general maternity ward cleanliness, improve the quality of physical facilities, and sensitize health providers for better communication with clients. Policy makers need to adopt strategies that ensure more women involvement in decision making and consideration of privacy and reassurance needs during the whole delivery process.